2021
DOI: 10.1038/s41467-021-24036-5
|View full text |Cite
|
Sign up to set email alerts
|

Defective folate metabolism causes germline epigenetic instability and distinguishes Hira as a phenotype inheritance biomarker

Abstract: The mechanism behind transgenerational epigenetic inheritance is unclear, particularly through the maternal grandparental line. We previously showed that disruption of folate metabolism in mice by the Mtrr hypomorphic mutation results in transgenerational epigenetic inheritance of congenital malformations. Either maternal grandparent can initiate this phenomenon, which persists for at least four wildtype generations. Here, we use genome-wide approaches to reveal genetic stability in the Mtrr model and genome-w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 89 publications
(183 reference statements)
8
47
0
Order By: Relevance
“…Since Mtrr gt/gt conceptuses at E10.5 derived from Mtrr gt/gt intercrosses showed a similar frequency of skewing (5.8% of conceptuses, p < 0.001) as F2 Mtrr +/+ conceptuses from the MGM pedigree (Figure 8B versus Figure 8C), the mechanism was likely due to Mtrr deficiency in one (or both) maternal grandparent. Notably, the frequency of skewing was greater in F2 Mtrr +/+ progeny when derived from an Mtrr +/gt MGM compared to an Mtrr +/gt MGF (Figure 8C versus Figure 8H) suggesting that the causative mechanism might be different when initiated via the F0 oocyte versus the F0 sperm, as was previously hypothesized (Blake et al, 2021). In further support of this hypothesis, we observed that severe conceptus misalignment occurred until at least until the F4 wildtype generation when derived from an F0 Mtrr +/gt female (Figures 8E,F) yet only until the F3 wildtype generation when derived from an F0 Mtrr +/gt male (Figures 8J,K).…”
Section: Conceptus Skewing Is Transgenerationally Inherited In the Mtrr Gt Mouse Linesupporting
confidence: 60%
See 4 more Smart Citations
“…Since Mtrr gt/gt conceptuses at E10.5 derived from Mtrr gt/gt intercrosses showed a similar frequency of skewing (5.8% of conceptuses, p < 0.001) as F2 Mtrr +/+ conceptuses from the MGM pedigree (Figure 8B versus Figure 8C), the mechanism was likely due to Mtrr deficiency in one (or both) maternal grandparent. Notably, the frequency of skewing was greater in F2 Mtrr +/+ progeny when derived from an Mtrr +/gt MGM compared to an Mtrr +/gt MGF (Figure 8C versus Figure 8H) suggesting that the causative mechanism might be different when initiated via the F0 oocyte versus the F0 sperm, as was previously hypothesized (Blake et al, 2021). In further support of this hypothesis, we observed that severe conceptus misalignment occurred until at least until the F4 wildtype generation when derived from an F0 Mtrr +/gt female (Figures 8E,F) yet only until the F3 wildtype generation when derived from an F0 Mtrr +/gt male (Figures 8J,K).…”
Section: Conceptus Skewing Is Transgenerationally Inherited In the Mtrr Gt Mouse Linesupporting
confidence: 60%
“…This nonconventional mode of inheritance is typically caused by exposure to an environmental stressor or metabolic disruption only in the initiating F0 generation and occurs independent of DNA basesequence mutations (Blake and Watson, 2016). The Mtrr gt mouse line is a known model of transgenerational epigenetic inheritance as several embryonic phenotypes are inherited by the wildtype grandprogeny and great grandprogeny when either maternal grandparent is a carrier for the Mtrr gt mutation (Padmanabhan et al, 2013;Blake et al, 2021). While the mechanism of epigenetic inheritance of phenotypes is unknown in the Mtrr gt model and other mammalian multigenerational models, it is particularly difficult to explore when the phenomenon occurs via the maternal lineage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations